1999
DOI: 10.1029/1999jd900785
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of diffusion upon the nonlinear behavior of the photochemistry of the mesopause region

Abstract: Abstract. The photochemical system of the mesopause region is a nonlinear driven oscillator enforced by the diurnal-periodic solar radiation. Under idealized conditions this oscillator can display nonlinear effects such as period doubling cascades or chaos. We investigate what happens if this system is subjected to atmospheric diffusion. A highresolution one-dimensional chemical system of the mesopause region has been established in order to answer this question. Strong diffusion destroys nonlinear effects, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…(21) points to the possible bi-stable behavior of the OH * layer peak. Realistic modeling at different parameters (e.g., water vapor, vertical eddy diffusion coefficient) related to the mesopause conditions infers period 2 oscillations that trigger 2-day variations in odd-oxygen / odd-hydrogen concentrations (Fichtelmann and Sonnemann, 1992;Sonnemann and Fichtelmann, 1997;Sonnemann and Feigin, 1999a, b;Sonnemann et al, 1999). Often, airglow measurements infer 2-day oscillations in the temperature and wind data in the mesopause region (e.g., Ward et al, 1996;Takahashi et al, 2005;López-González et al, 2009;Pedatella and Forbes, 2012, and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…(21) points to the possible bi-stable behavior of the OH * layer peak. Realistic modeling at different parameters (e.g., water vapor, vertical eddy diffusion coefficient) related to the mesopause conditions infers period 2 oscillations that trigger 2-day variations in odd-oxygen / odd-hydrogen concentrations (Fichtelmann and Sonnemann, 1992;Sonnemann and Fichtelmann, 1997;Sonnemann and Feigin, 1999a, b;Sonnemann et al, 1999). Often, airglow measurements infer 2-day oscillations in the temperature and wind data in the mesopause region (e.g., Ward et al, 1996;Takahashi et al, 2005;López-González et al, 2009;Pedatella and Forbes, 2012, and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the influence of vertical eddy diffusion on MPCS evolution performed by Sonnemann and Feigin (1999) and Sonnemann et al (1999) revealed that transport reduces appreciably the spectrum of possible modes of behavior of this system. It was found that for the values of the vertical diffusion coefficient (5-20) m 2 s −1 observed in the mesopause region in summer (e.g.…”
Section: Mesospheric Photochemical System and Its Nonlinear Dynamic Pmentioning
confidence: 99%
“…These parameters, in turn, depend on altitude. In the works by Sonnemann et al (1999) and Sonnemann and Feigin (1999), it was demonstrated that it is sufficient to take this dependence into consideration in the mesopause region only for the air concentration and photolysis rate of molecular oxygen.…”
Section: Mesospheric Photochemical System and Its Nonlinear Dynamic Pmentioning
confidence: 99%
See 2 more Smart Citations